A case report with high bilirubinemia and hemolytic anemia during leptospirosis and a short review of similar cases - Edmond Puca; Erjona Abazaj; Pellumb Pipero; Arjan Harxhi; Redi Ferizaj; Najada Como; Entela Lamcaj (Babol University of Medical Sciences, 2020)
Background: Leptospirosis is characterized by very diverse clinical manifestations, which may range from flu-like subclinical forms to very severe presentations characterized by multi-organ failure, or to atypical presentations. One of its most aggressive presentations is Weil's disease, characterized by jaundice, hemorrhagic phenomena and renal failure. Cases with high bilirubinemia over 30mg/dL aren't communes in human leptospirosis. Our aims are to present an atypical case presentation of human leptospirosis, characterized by jaundice and hemolytic anemia, and to make a short review in PubMed for similar cases. At the same time we want to emphasize the diversity of the clinical presentation of human leptospirosis Methods: A 54-year-old man presents at the emergency department of the infectious medicine with severe fatigue, nausea, vomiting, and generalized weakness. On exam, he was alert and well oriented, blood pressure was 80/50 mmHg and icteric. First blood examinations confirmed high bilirubinemia, thrombocytopenia and acute renal failure. Results: Based on anamnestic and clinical evaluations, blood and serology examinations, the patients resulted with leptospirosis. The bilirubin reached 73.4mg/dL. At the same time on PubMed research we found only limited cases with leptospirosis associated with bilirubinemia over 30mg/dL and over less with hemolytic anemia.   Conclusions: Based on our clinical experience, as well as literature data, we suggest that clinicians should have a high index of suspicion in cases of jaundice with exposure possibilities for infectious diseases. Connection of high bilirubinemi over then 30mg/dL and hemolytic anemia in human leptospirosis is an uncial case report.